Association Between AIM2 and Pycard Genes Polymorphisms and Susceptibility to Periodontitis with Coronary Heart Disease - Ali Daily Z; Al-Ghurabi BH; Al-Qarakhli AMA; Hussein HM (Dove Medical Press, 2023)
Zina Ali Daily,1 Batool Hassan Al-Ghurabi,2 Ahmed Makki A Al-Qarakhli,3 Hashim Mueen Hussein4 1Department of Periodontics, College of Dentistry, University of Baghdad, Baghdad, Iraq; 2Department of Basic Science, College of Dentistry, University of Baghdad, Baghdad, Iraq; 3Department of Oral Diagnosis, College of Dentistry, University of Anbar, Baghdad, Iraq; 4Department of Conservative Dentistry, College of Dentistry, University of Mustansiriyah, Baghdad, IraqCorrespondence: Hashim Mueen Hussein, Department of Conservative Dentistry, College of Dentistry, Mustansiriyah University, Box 14022, Baghdad, Iraq, Email hashimmueenhussein@gmail.com; hashimmueenhussein@uomustansiriyah.edu.iq Zina Ali Daily, Department of Periodontics, College of Dentistry, University of Baghdad, Baghdad, Iraq, Email alizena046@gmail.comBackground: Numerous genetic variations in inflammasome components are linked to prevalent disorders in the general population, including periodontitis and cardiovascular illness. Polymorphisms in the genes play a critical in the initiation and development of inflammatory diseases. The limited study on AIM2 gene variation associated with inflammatory disease and no study of PYCARD gene variation associated with inflammatory disease.Objective: This case-control study was to examine the association between the single nucleotide polymorphism of AIM2 and Pycard genes with susceptibility to periodontitis with and without coronary heart disease, to determine interleuken-18 and gasdermin D levels in the saliva of periodontitis with and without coronary heart disease patients, as well as their correlation with salivary interleuken-18 and gasdermin D levels and clinical periodontal parameters.Methods: The present study recruited 120 participants: 30 were healthy subjects (control, C), 30 had generalized periodontitis (P), 30 had atherosclerosis coronary heart disease with clinically healthy periodontium (AS-C), and 30 had atherosclerosis coronary heart disease with generalized periodontitis (AS-P). All individuals’ demographic data recorded, saliva and blood samples collected, then periodontal characteristics were detailed. These parameters include plaque index, bleeding on probing, probing pocket depth, and clinical attachment loss. AIM2 and Pycard gene polymorphisms were analyzed by polymerase chain reaction assay, electrophoresis and sequencing. An enzyme-linked immunosorbent assay (ELISA) was conducted to determine the level of interleuken-18 and gasdermin D in their saliva.Results: The study result of high frequency (T) in single-nucleotide polymorphisms. The high genotypes distribution of GT and TT genotypes in the AIM2 gene and the CT and TT genotypes in the Pycard gene were detected in the periodontitis, atherosclerosis coronary heart disease with healthy periodontium and atherosclerosis coronary heart disease with generalized periodontitis groups as compared to control group. Elevation of salivary interleuken-18 and gasdermin D levels in three patients’ groups compared to healthy controls. Both these single-nucleotide polymorphisms also significantly correlated with higher salivary interleuken-18 and gasdermin D levels and worse clinical indices of periodontitis.Conclusion: Single-nucleotide polymorphisms in the AIM2 and Pycard genes are associated with an increased risk of developing periodontitis with and/or without coronary heart disease. Elevation of salivary interleuken-18 and gasdermin D levels associated and impacted on periodontitis with and/or without coronary heart disease. These single-nucleotide polymorphisms may provide evidence for a genetic role in the pathogenesis of periodontitis with and without atherosclerosis coronary heart disease.Keywords: periodontitis, coronary heart disease, single nucleotide polymorphisms, interleuken-18, gasdermin D